2004
DOI: 10.1073/pnas.0401064101
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of functionally normal and malignant human breast tissues in mice

Abstract: The study of normal breast epithelial morphogenesis and carcinogenesis in vivo has largely used rodent models. Efforts at studying mammary morphogenesis and cancer with xenotransplanted human epithelial cells have failed to recapitulate the full extent of development seen in the human breast. We have developed an orthotopic xenograft model in which both the stromal and epithelial components of the reconstructed mammary gland are of human origin. Genetic modification of human stromal cells before the implantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
631
2
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 697 publications
(663 citation statements)
references
References 28 publications
15
631
2
9
Order By: Relevance
“…The importance of locally produced rather than systemic IGF1 is also supported by the observation that mammary branching proceeds normally in mice with a liver-specific IGF1 deletion that results in a 75% decrease in circulating IGF1 levels without affecting mammary-specific IGF1 production [15]. On the other hand, mammary branching is impeded in global IGF1 knockout mice lacking both systemic and local IGF1 production.…”
Section: What Cues Act Upstream Of the Adam17-areg-egfr Axis?mentioning
confidence: 90%
See 1 more Smart Citation
“…The importance of locally produced rather than systemic IGF1 is also supported by the observation that mammary branching proceeds normally in mice with a liver-specific IGF1 deletion that results in a 75% decrease in circulating IGF1 levels without affecting mammary-specific IGF1 production [15]. On the other hand, mammary branching is impeded in global IGF1 knockout mice lacking both systemic and local IGF1 production.…”
Section: What Cues Act Upstream Of the Adam17-areg-egfr Axis?mentioning
confidence: 90%
“…And, as is true in mice, stromal factors are also apt to influence human breast development. Indeed, human breast epithelial cells will only form functional glandular structures if they are transplanted to 'humanized' mouse mammary fat pads that contain human breast fibroblasts [15] or if they are transplanted within collagen matrix gels that also contain normal human or mouse mammary fibroblasts [16]. Thus, stromal celland matrix-derived signals appear to play a critical role in mammary ductal development, which raises obvious questions concerning what stromal factors are involved and how they influence the developing epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Many functional studies have demonstrated the importance of fibroblasts in cancer initiation 1 , progression [2][3][4] and metastases 5 . In animal models of prostate and breast cancers, oncogene-modified epithelial cells became malignant or showed enhanced growth when coinoculated with fibroblasts that were either oncogene induced 6 or derived from fresh human carcinoma tissues 2,3 (that is, CAFs).…”
mentioning
confidence: 99%
“…This experiment suggests that non-cell autonomous factors may play an important role in breast cancer etiology. Indeed, recent evidence that an altered stromal environment can enhance mammary tumor formation supports this hypothesis (Kuperwasser et al 2004).…”
Section: Using Defined Genetic Elements To Model Specific Cancer Typesmentioning
confidence: 93%